Massage therapy training for daycare caregivers to stimulate children’s mental health in Dago Area - Meta Maulida Damayanti; Yuktiana Kharisma; Ayu Prasetia; Ermina Widiyastuti; Meike Rachmawati; Ismet Muchtar Nur; Abdul Hadi Hassan (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2023)
Massage therapy has been shown to be highly effective in preventing premature birth, encouraging infant growth, increasing attention, reducing depression and aggression, treating motor problems, and reducing discomfort. Daycare is a partner institution for parents in childcare that synergizes in observing the growth and development of children's mental health. This community service program aims to increase knowledge about children's mental health, and training and mentoring regarding relaxing massage for children. This service activity plan consists of the preparation, implementation, and evaluation stages. The methods to be carried out vary from giving interactive materials, demonstrations, discussions, and practice. This activity was attended by 24 caregivers, 2 presenters, and 6 community service teams. This program was attended by caregivers aged between 22-50 years, with most of them being married, the highest education level being high school (75%), and the most work experience under 3 years (67%). Based on the results of the evaluation, all participants benefited from the knowledge training on child mental development and the application of baby massage in carrying out their daily duties as caregivers at daycare centers. Training childcare practitioners' metallization and helping them achieve attitude-based metallization is effective in helping them better understand child development.